2010
DOI: 10.4084/mjhid.2010.003
|View full text |Cite
|
Sign up to set email alerts
|

Use of Hematopoietic Growth Factor in the Management of Hematological Side Effects Associated to Antiviral Treatment for HCV Hepatitis

Abstract: Haematological abnormalities are common during combination antiviral therapy for chronic hepatitis C. Although dose reduction or discontinuation can easily treat these side effects, they can adversely affect the efficacy of combination antiviral therapy reducing the likelihood of a sustained viral response (SVR). To avoid potentially diminishing a patient’s chance of response, many physicians have begun using growth factors off-label to manage anaemia and neutropenia in hepatitis C. Haematopoietic growth facto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 79 publications
0
2
0
Order By: Relevance
“…Hepatitis C treatment is evolving from interferon-based therapy (IFN) 1–2 to direct antiviral agents (DAA), which have been shown to be highly effective with very few adverse events, 1 , 2 so, unlike interferon, 3 they can be safely administered, without growth factors, even in the presence of thrombocytopenia and anemia, 2 , 4 but may have some dangerous extra-hematological adverse effects, currently little known. In 2015 the Food and Drug Administration and the European Medical Agency added information to the Harvoni (ledipasvir / sofosbuvir) and Sovaldi (sofosbuvir) labels about the serious slowing of the heart rate of amiodarone when taken in combination with another direct acting antiviral for the treatment of hepatitis C infection.…”
Section: Dear Editormentioning
confidence: 99%
“…Hepatitis C treatment is evolving from interferon-based therapy (IFN) 1–2 to direct antiviral agents (DAA), which have been shown to be highly effective with very few adverse events, 1 , 2 so, unlike interferon, 3 they can be safely administered, without growth factors, even in the presence of thrombocytopenia and anemia, 2 , 4 but may have some dangerous extra-hematological adverse effects, currently little known. In 2015 the Food and Drug Administration and the European Medical Agency added information to the Harvoni (ledipasvir / sofosbuvir) and Sovaldi (sofosbuvir) labels about the serious slowing of the heart rate of amiodarone when taken in combination with another direct acting antiviral for the treatment of hepatitis C infection.…”
Section: Dear Editormentioning
confidence: 99%
“…Particularly, maintaining RBV dose is critical in patients with chronic hepatitis C who are treatment naive or who did not respond to a previous course of antiviral therapy. [8][9][10] Several data indicate that the dose of RBV is very important in preventing relapse. 8 A recent study demonstrated that patients treated with a weight-based RBV had a lower relapse rate than patients receiving fixed doses, especially in patients with high body weight.…”
Section: Introductionmentioning
confidence: 99%